An Examination of Preterm Birth and Residential Social Context among Black Immigrant Women in California, 2007–2010. - Blebu, Bridgette E.; Ro, Annie; Kane, Jennifer B.; Bruckner, Tim A. (Journal of Community Health, 2019)
The foreign-born black population contributes a considerable amount of heterogeneity to the US black population. In 2005, black immigrants accounted for 20% of the US black population. Compared to native-born black women, black immigrant women are at lower risk for adverse birth outcomes, including preterm birth. Some scholars posit that differential exposures to socioeconomic disadvantage and structural racism in the residential context may account for this advantage. However, to date, few studies offer comprehensive examinations of the black immigrant residential social context, particularly in settlement regions beyond predominantly black and historically segregated regions. Further, studies examining the black immigrant residential context typically use a single indicator, which limits discussion of the intersecting domains that simultaneously increase or decrease risk among black immigrants. We addressed these gaps by examining black immigrant neighborhoods in the state of California, where racial residential segregation of the black population is low. We operationalized the residential context of black immigrant women using three distinct attributes: immigrant co-ethnic density, black racial concentration, and neighborhood deprivation. We linked 2007–2010 California birth records of black immigrant women and 2010 census data on tract-level social attributes (N = 6930). OLS regression analyses showed that immigrant co-ethnic density, black racial concentration and neighborhood deprivation were not associated with preterm birth among black immigrants. Our findings indicate that in California, residential social context has little relation to black immigrant preterm birth—a finding that is unique compared to residential settings of other settlement contexts.